Cross-country and regional Analyses on the effect of environmental accounting on financial profitability, liquidity, marketability, leverage, and firm value of environmentally sensitive industries across the ASEAN-5 - Delos Reyes, Venz Luis D.M. (Animo Repository, 2021)
As one of the environmental hubs of the world, the operations of Southeast Asian companies inevitably coincide with the environment which leads to calls for environmental accountability. The main objective of this empirical research is to determine the effects of environmental disclosures and environmental costs reporting to the financial profitability, liquidity, marketability, leverage, and firm value of listed chemical, energy, food, beverage and tobacco (FBT), metals and mining, and utilities companies in Malaysia, Indonesia, Philippines, Thailand and Singapore, and in the whole ASEAN-5 region. The researchers make use of voluntary disclosure, legitimacy, signaling, stakeholders, and institutional theories to explain, predict and understand relationships. Also, the moderating effects of the firm-specific characteristics on each of the relationships mentioned are likewise explored and tested. Panel regression analysis is used by the researchers. Results show that environmental accounting disclosure has a significant direct effect on NPM, ROE, MBR and TQ. Moreover, EAD has no significant effect on CR, QR, and PER, but when moderated by firm specific characteristics, it has a significant effect on CR, QR, PER, and DTE in some countries. Environmental costs, on the other hand, have a significant effect on NPM, PER, MBR, and TQ. Likewise, environmental costs have a significant effect on ROE, CR, QR, and PER in some countries, at some extent, when moderated by firm-specific characteristics. In the context of the ASEAN-5 region, findings of this study suggest that EAD has a significant effect only on firm value using Tobin’s Q. But when moderated by firm-specific characteristics except years of existence, EAD has a significant effect on NPM, ROE, CR, QR, and MBR. On the flip side, environmental cost has no significant effect on a company's financial performance. But when moderated by auditor type, industry type, years as publicly listed, and years of existence, it has a significant effect on NPM, ROE, and TQ. Furthermore, numerous recommendations are directly addressed to the internal and external users of financial and non-financial information, regulatory bodies and the academe.